Travels in Siberia - Frazier, Ian (Farrar, Straus and Giroux, 2010)
In Travels in Siberia, Ian Frazier trains his eye for unforgettable detail on Siberia, that vast expanse of Asiatic Russia. He explores many aspects of this storied, often grim region, which takes up one-seventh of the land on earth. He writes about the geography, the resources, the native peoples, the history, the forty-below midwinter afternoons, the bugs. More than just a historical travelogue, Travels in Siberia is also an account of Russia since the end of the Soviet Union and a personal reflection on the all-around amazingness of Russia, a country that still somehow manages to be funny--Publisher description.